2020
DOI: 10.1089/end.2019.0545
|View full text |Cite
|
Sign up to set email alerts
|

Renal Stone Features Are More Important Than Renal Anatomy to Predict Shock Wave Lithotripsy Outcomes: Results from a Prospective Study with CT Follow-Up

Abstract: Introduction: Lower pole kidney stones have been associated with poor shock wave lithotripsy (SWL) outcomes because of its location. However, the real impact of collecting system anatomy on stone clearance after SWL is uncertain. There is a lack of prospective well-controlled studies to determine whether lower pole kidney stones have inferior outcomes than nonlower pole kidney stones when treated with SWL. Methods: We prospectively evaluated patients with a single kidney stone of 5-15 mm undergoing SWL from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…At the very best, SFRs were at the bottom end of the range of previous reports of first-line SWL or RIRS. [9][10][11]24,25 Some of the explanation for that is we report SFR mainly based on NCCT (81.8% of the SWL group and 100% of the RIRS group), whereas other reports were based mainly on ultrasound plus KUB. 26 Other possible explanation is that standard PCNL may alter normal collecting system anatomy and influence SFR of a second-line therapy.…”
Section: Residual Fragments After Pcnl: Swl Vs Rirsmentioning
confidence: 67%
See 2 more Smart Citations
“…At the very best, SFRs were at the bottom end of the range of previous reports of first-line SWL or RIRS. [9][10][11]24,25 Some of the explanation for that is we report SFR mainly based on NCCT (81.8% of the SWL group and 100% of the RIRS group), whereas other reports were based mainly on ultrasound plus KUB. 26 Other possible explanation is that standard PCNL may alter normal collecting system anatomy and influence SFR of a second-line therapy.…”
Section: Residual Fragments After Pcnl: Swl Vs Rirsmentioning
confidence: 67%
“…Patients were discharged 2 hours after the end of the procedure if VAS for pain was >3 with oral analgesics for 7 days and alpha-blockers for 30 days. 11 SFR defined as no stone fragments and success rate defined as £2 mm were evaluated on POD 90 by NCCT or ultrasound and kidney, ureter, and bladder radiograph (KUB) for each renal unit. 16 Surgical complications based on Clavien-Dindo classification during the 90 days of follow-up were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SWL stone-free rates are more influenced by stone burden and composition and by patient's body habitus, overall obesity as well as renal anatomy as previously stated (38). Many studies comparing the results of SWL, FURS and PCNL have been published and some of them are summarized in Table-2 (39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Treatment Of Lower Pole Stones 10-20mmmentioning
confidence: 77%
“… 15 17 18 A recent prospective study with CT follow-up also reported that renal stone features are more critical than renal anatomy in predicting the outcomes of shockwave lithotripsy. 19 …”
Section: Discussionmentioning
confidence: 99%